Controle da podridão azul em maçãs utilizando revestimento comestível elaborado com composto antifúngico de levedura antagonista - Ferreira, Fabiana Fiusa (2020)
Blue mold, caused by Penicillium expansum, is the most common post-harvest rot disease in apples. Food coating and biological control agents, such as killer yeasts, are alternative strategies to reduce post-harvest losses. This dissertation aimed to investigate the control of blue rot in apples with an edible coating containing yeast killer toxins. A preliminary test was performed with 80 fruits to determine the order of coating application, fruit wounding procedures, and sampling intervals. The experiment consisted of three treatments (CF, fruits coated with an aqueous solution edible coating; KCF, fruits coated with an edible coating containing yeast killer toxins; and UF, uncoated fruits), totaling 279 fruits. After coating application, the fruits were wounded and inoculated with 10 µL suspension containing 105 conidia of P. expansum per milliliter. Fruits were stored at 25 °C for 12 days and evaluated at 2- day intervals for determination of the percentage of diseased fruits, infected wounds, and wound closure. Physicochemical parameters (pH and soluble solids) and fruit weight loss were also determined. Coatings were examined by scanning electron microscopy. The coating containing antifungal compounds did not decrease rot incidence or wound infection rate but reduced disease severity, as shown by the 47.6% wound closure in KCF compared with 10.5% in CF. Wound closure was significantly higher in KCF from the fourth day of storage onward, reaching 54.1% after 12 days. CF showed a wound closure of only 12.7% at the end of the storage period. Fruit pH remained practically stable during storage, with a variation of 0.3 in UF, in CF, and in KCF. During the 12 days of storage, soluble solids increased by 2.1, 3.8, and 2.4 °Brix in UF, CF, and KCF, respectively. These results indicate that physicochemical properties were not limiting factors for fungal development and suggest that fungal control was achieved through the protective and antagonistic effects of the coatings. CF and KCF showed a lower weight loss than UF after 12 days of storage. Antifungal compounds present in KFC were effective in inhibiting P. expansum mycelial development, showing great potential for the post-harvest control of blue mold in apples.